2020
DOI: 10.3390/app10207355
|View full text |Cite
|
Sign up to set email alerts
|

New Aspects of Socioeconomic Assessment of the Railway Infrastructure Project Life Cycle

Abstract: The paper deals with the issue of evaluation of socioeconomic impacts of occurrences emerging from railway infrastructure. The presented research results form part of a broader research subject focusing on the evaluation of the socioeconomic benefits of projects for the implementation of measures aimed at increasing the safety and reliability of railway infrastructure. The research topic addresses a part of the evaluation of railway infrastructure project efficiency within its life cycle using the cost–benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…(2020) indicated that the economic and market issues were the main factors to be studied in the feasibility study of a railway construction project (Mohammed et al ., 2019). Hromádka et al. (2020) addressed the issue of evaluation of socioeconomic impacts of occurrences emerging from railway infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2020) indicated that the economic and market issues were the main factors to be studied in the feasibility study of a railway construction project (Mohammed et al ., 2019). Hromádka et al. (2020) addressed the issue of evaluation of socioeconomic impacts of occurrences emerging from railway infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The parameters of the average occurrence in passenger transport can be derived from the Database of Occurrences [19]. The average occurrence in passenger transport causes the following societal impacts, which are derived from the database of Occurrences [19] using the approach defined in [21,22] where: UI P -unit impact (unit impact of the average occurrence in passenger transport, CZK/occurrence), AIH 𝑖 -average impact on health (average impact of the occurrence in passenger transport on health: 1 -fatalities, 2 -serious injuries, 3 -minor injuries, CZK/occurrence), AITD P -average impact on transport delay (average impact of the occurrence in passenger transport on travel delay, CZK/occurrence), AML P -average material loss (average material loss by the occurrence in passenger transport, CZK/occurrence).…”
Section: Passenger Rail Transportmentioning
confidence: 99%
“…The parameters of the average occurrence in freight transport can be derived from the Database of Occurrences [19]. The average occurrence in freight transport causes the following societal impacts, which are derived from the database of Occurrences [19] using the approach defined in [21,22]:…”
Section: Freight Rail Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction project should consider cost management approaches from the buildings' whole life cycle perspective. Life cycle cost management plays an important role that focuses on cost optimization [1]. However, this approach has more potential for use than is currently utilized.…”
Section: Introductionmentioning
confidence: 99%